Energy Transfer Between Hot Protons and Electromagnetic Ion Cyclotron Waves in Compressional Pc5 Ultra‐low Frequency Waves. Issue 5 (27th April 2021) - Kitamura, N.; Shoji, M.; Nakamura, S.; Kitahara, M.; Amano, T.; Omura, Y.; Hasegawa, H.; Boardsen, S. A.; Miyoshi, Y.; Katoh, Y.; Teramoto, M.; Saito, Y.; et al.
Abstract: The Magnetospheric Multiscale (MMS) spacecraft observed many enhancements of electromagnetic ion cyclotron (EMIC) waves in an event in the late afternoon outer magnetosphere. These enhancements occurred mainly in the troughs of magnetic field intensity associated with a compressional ultralow frequency (ULF) wave. The ULF wave had a period of ∼2–5 min (Pc5 frequency range) and was almost static in the plasma rest frame. The magnetic and ion pressures were in antiphase. They are consistent with mirror‐mode type structures. We apply the Wave‐Particle Interaction Analyzer method, which can quantitatively investigate the energy transfer between hot anisotropic protons and EMIC waves, to burst‐mode data obtained by the four MMS spacecraft. The energy transfer near the cyclotron resonance velocity was identified in the vicinity of the center of troughs of magnetic field intensity, which corresponds to the maxima of ion pressure in the compressional ULF wave. This result is consistent with the idea that the EMIC wave generation is modulated by ULF waves, and preferential locations for the cyclotron resonant energy transfer are the troughs of magnetic field intensity. In these troughs, relatively low resonance velocity due to the lower magnetic field intensity and the enhanced hot proton flux likely contribute to the enhanced energy transfer from hot protons to the EMIC waves by cyclotron resonance. Due to the compressional ULF wave, regions of the cyclotron resonant energy transfer can be narrow (only a few times of the gyroradii of hot resonant protons) in magnetic local time. Key Points: Electromagnetic ion cyclotron wave enhancements were detected in a compressional ultralow frequency (ULF) wave Troughs of magnetic field intensity of the ULF wave are preferential locations for the cyclotron resonant energy transfer Due to compressional ULF wave, regions of the cyclotron resonant energy transfer can be narrow in magnetic local time